BK viremia and nephropathy in pediatric renal transplant recipients. (4th July 2019) - Hamasaki, Yuko; Dolan, Niamh M.; Cubitt, David; Breuer, Judith; Sebire, Neil J.; Marks, Stephen D.
Abstract: The renal survival rate of pediatric renal transplant recipients (pRTR) has improved with the use of modern immunosuppressive agents; however, the incidence of post‐transplantation viral infection has increased. This study investigated the incidence of BK viremia and BK viral–associated nephropathy (BKVAN) in pRTR. One‐hundred‐and‐thirty‐four pRTR were divided into two groups: group 1 (n = 20, 14.9%) comprised those who were prospectively followed with longitudinal analyses after renal transplantation in the time period from May 2007 to June 2008, while group 2 (n = 114, 85.1%) cross‐sectional study of those who were transplanted from January 1994 to April 2007. The mean ages at transplantation in groups 1 and 2 were 10.6 ± 4.7 years and 7.8 ± 4.5 years, respectively. BK viremia was detected in four (20.0%) patients in group 1, and seven (6.1%) in group 2 ( P  = 0.04), with increased incidence associated with induction therapy. The median time to detection of BK viremia after transplantation was 44 days in group 1 and 142 days in group 2. BKVAN was diagnosed in three patients (two in group 1 and one in group 2). All three patients diagnosed with BKVAN were receiving tacrolimus, mycophenolate mofetil, and corticosteroids as maintenance immunosuppression. Reducing immunosuppression resulted in reduced BK viremia. Monitoring for BK viremia and BKVAN is important in pRTR being treated with the current immunosuppressive regimen. The first line of treatment for BK viremia remains careful reduction of immunosuppression and close monitoring of renal allograft function.